Flow, Work Satisfactions and Psychological Well-Being among Nurses in Turkish Hospitals - Ronald J Burke; Mustafa Koyuncu; Lisa Fiksenbaum (Archives of Nursing Practice and Care - Peertechz Publications, 2016)
This exploratory study examined the relationship between the experience of flow at work and indicators of satisfaction, engagement and psychological well-being of nursing staff working in Turkish hospitals. This emphasis was consistent with emerging trends in both psychology and organizational studies, termed positive psychology or positive organizational scholarship respectively, to focus on strengths and excellence rather than dissatisfaction and pathology. Data were collected from 224 staff nurses in Ankara Turkey using anonymously completed questionnaires, a 37% response rate. Hierarchical regression analyses, controlling for both personal demographic and work situation characteristics, indicated that flow accounted for significant increments in explained variance on most work outcome measures but not on indicators of psychological well-being. Explanations for the association of flow with favorable outcomes are offered along with potentially practical implications.